Composting of selected organic wastes from peri-urban areas of Harare, Zimbabwe - Rangarirayi L Mhindu; Menas Wuta; Esther Ngorima (International Journal of Recycling of Organic Waste in Agriculture)
Background: The composting process of peri-urban household wastes, changes that occur during composting, and the properties of the composting products that are of importance for use as soil amendments were studied. Seven different composting mixtures were made in large piles consisting of fallen tree leaves and fresh vegetable leaves mixed with grass or maize straw (0%, 10%, 30% and 50% w/w), wastes common in peri-urban areas of Harare. Results: The highest temperature peaks of the mixtures with 0% and 10% straw were in the range of 68°C to 72°C. Mixtures with 30% straw had temperature peaks of 50°C (maize) and 52°C (grass). The mixture with 50% grass straw reached a peak of 50°C, while the corresponding mixture with maize straw did not reach thermophilic temperatures. pH ranged from between 6.2 and 6.8 before composting to between 7.4 and 7.8 after composting. The ammonium concentration peaked at various times but declined to negligible concentrations at day 140. The concentration of nitrates increased with composting up to day 97 and decreased gradually thereafter. There was a general increase in nitrogen concentration from 0.9% to 2.3% as composting progressed. Decreases in organic C% and C/N ratio with composting were also observed, signifying mass loss. Conclusion: The results of this study indicated that household wastes with 50% straw or less can be composted but with measures being taken to achieve temperatures greater than 55°C for at least 3 days to destroy weed seeds and pathogens. The composts with 30% straw mixture had the greatest potential as a soil amendment in peri-urban areas of Harare as they effectively reduced nitrogen losses.